The influence of leadership, work environment and organizational culture on lecturer productivity in publishing scientific papers with motivation as a moderating variable - Yohanes B.W. Thalibana; Henny A. Manafe; Simon Sia Niha (Jurnal Mantik, 2023)
The achievement of a lecturer in research and publication is the main benchmark that illustrates the professionalism of lecturers as scientists, so an analysis is needed related to variables that affect lecturer productivity. This type of research is quantitative research and the data is analyzed by statistical methods. Data collection using a questionnaire. Data analysis uses descriptive statistical analysis and inferential statistical analysis. The hypothesis built is that leadership, work environment and organizational culture each have a positive and significant effect on productivity with motivation acting as moderation. The results of inferential statistical tests of the effect of leadership on productivity, the effect of the work environment on productivity, the effect of organizational culture on productivity, the t-statistic test values are all greater than the t-table value of 1.96, with the alpha level value of all variables below 5%. The results of inferential statistical tests of the role of motivation moderating leadership and organizational culture on productivity obtained a t-statistic value smaller than the t-table value of 1.96 as well as the P Value of the two variables greater than the value of the alpha level of 5%. Motivation moderates the work environment on productivity obtained t-statistic test results greater than the t-table 1.96 with an alpha level value below 5%. The results showed leadership, work environment, organizational culture has a positive and significant influence on productivity. The role of motivation cannot moderate leadership and organizational culture on productivity and the role of motivation can moderate the work environment on productivity.